2013
DOI: 10.1177/193229681300700430
|View full text |Cite
|
Sign up to set email alerts
|

Using Avatars to Model Weight Loss Behaviors: Participant Attitudes and Technology Development

Abstract: Abbreviations: (BMI) body mass index, (SD) standard deviation, (VR) virtual realityKeywords: eating behavior, exercise behavior, intervention, models, obesity, overweight

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 49 publications
(74 reference statements)
1
47
0
3
Order By: Relevance
“…Additional hand review of these articles produced two more articles for consideration, for a total of 28 articles reviewed. Authors CYO and CRL excluded one of these articles because the technology-based solution was not designed specifically for people with diabetes, per se, and was therefore not tested with that user group [8]. These authors then excluded three more articles because the technology-based solution collected and transmitted patient data to providers (i.e., telemonitoring) without offering either a patient-facing component that allowed patients to track self-care or a close-looped system in which patient data was then used to educate or provide patients with self-care support [911].…”
Section: Methodsmentioning
confidence: 99%
“…Additional hand review of these articles produced two more articles for consideration, for a total of 28 articles reviewed. Authors CYO and CRL excluded one of these articles because the technology-based solution was not designed specifically for people with diabetes, per se, and was therefore not tested with that user group [8]. These authors then excluded three more articles because the technology-based solution collected and transmitted patient data to providers (i.e., telemonitoring) without offering either a patient-facing component that allowed patients to track self-care or a close-looped system in which patient data was then used to educate or provide patients with self-care support [911].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, VR interventions primarily involved delivery of traditional face-to-face treatment in a virtual environment with group leaders and patients attending and participating in avatar form. 10,11 The avatars were customized with a patient's appearance to demonstrate basic weight management behaviors (eg, walking on a treadmill at medium intensity), 9 or using VR as an adjunct to face-to-face treatment to reinforce skills training and change weightrelated cognitions. 13 Because the ES system is automated, requires no special equipment (eg, goggles), and is designed for web-based delivery, it may someday be possible to provide experiential training in weight management skills to large numbers of patients at low cost via technology they already own (eg, PCs, tablets, smartphones).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A few early studies showed that VR could be used for these purposes, but most relied on a human counselor to guide the experience, thus limiting their reach and increasing cost. [9][10][11] The goal of the Experience Success (ES) project was to develop a system for creating and deploying automated VR scenarios for online training in BWL skills, and collect feedback from test users with an initial social eating scenario.…”
Section: Obesity Technologymentioning
confidence: 99%
“…Studies in the area have shown that users have a better understanding of how their choices can affect their health, leading to changes in behavior and having an impact on obesity, for instance. Also, studies that assess the use of new technologies by elderly people reveal that this population is also capable of learning how to use these resources, with positive effects on cognition and quality of life [11][12][13].…”
Section: Texto Em Portuguêsmentioning
confidence: 99%
“…Estudos na área tem mostrado que os usuários entendem melhor como as escolhas podem afetar a sua saúde, resultando em modificação de comportamentos e tendo impacto sobre a obesidade, por exemplo. Ainda, estudos que avaliam o uso das novas tecnologias pelos idosos mostram que essa população também tem condições de assimilar o uso desses recursos, inclusive com efeitos positivos na cognição e na qualidade de vida [11][12][13].…”
unclassified